Fundamentals Of Entrepreneurship (ENT300) : Sal Safiyya Group Sdn. Bhd. / Sabreena Wam … [et al.] - Wam, Sabreena; Sa’adan, Azlin; Azlan, Nurul Faezah (2017)
Sal Safiyya Group Sdn. Bhd. is a boutique that provides women and kids apparels based in Kota Samarahan. The business started by two siblings who are currently the shareholders, Nur Salmizar binti Azmi and Izuan Izzani bin Azmi. Sal Safiyya Group Sdn. Bhd. has 8 employees who help to run the business. Sal Safiyya boutique concept is Muslimah apparels that can be wore by anyone. Sal Saffiya Group Sdn. Bhd. focuses on the qualities of the apparels that gives comfort to the wearer. Sal Saffiya boutique hand-pick their materials themselves which make their products more special than the others. Sal Safiyya boutique also provides seasonal collections.